OP20 Twenty-five years and not much has changed: trends in sociodemographic inequalities in breastfeeding initiation in Great Britain. (13th September 2016) - Simpson, DA; Carson, C; Kurinczuk, JJ; Quigley, MA
Abstract : Background: While survey data show that breastfeeding initiation rates in England, Wales and Scotland (Great Britain) increased, there remains limited evidence regarding trends in sociodemographic inequalities in initiation. This study examined whether sociodemographic inequalities in breastfeeding initiation had changed over 25 years in Great Britain. Methods: Data from the 1985, 1990, 1995, 2000, 2005 and 2010 UK Infant Feeding Surveys were analysed. We included a nationally representative sample of 53, 980 mothers who gave birth to babies in Great Britain in any of the survey years. Measures of maternal sociodemographic circumstances included age at delivery, age at completion of full-time education, partnership status, socioeconomic classification and country of residence. Changes in maternal sociodemographic status from 1985 to 2010 were described. Logistic regression estimated the effects of sociodemographic circumstances against breastfeeding initiation at each survey year. The resulting odds ratios (ORs) were assessed for changes in inequalities in initiation over time. Results: The sociodemographic circumstances of mothers changed markedly between 1985 and 2010. Mothers in 2010 were older; more highly educated (51% with full-time education beyond age 18 compared with 14% in 1985); of higher socioeconomic status (35% in the highest socioeconomic class compared with 6% in 1985); and more likely to be unmarried (43% cohabitating or single compared with 19% in 1985). Breastfeeding initiation also rose from 64% to 81% over this period. There were significant sociodemographic inequalities in initiation in every survey year. The proportion of mothers who initiated breastfeeding increased significantly with increases in age at delivery, education and socioeconomic classification (p < 0.001). These effects were fairly constant across the study period. For example, the odds of breastfeeding initiation were about twice as high when full-time education was completed beyond age 18 compared with age 17–18, in 1985 (adjusted OR 2.0, 95% CI: 1.5–2.6) and 2010 (adjusted OR 2.4, 95% CI: 2.0–2.8). The results also suggest a slight reduction in the effect of socioeconomic circumstances over time; however, the effect remained statistically significant in 2010 for the highest class compared to the manually-skilled class: adjusted ORs ranged from 2.2 (95% CI: 1.6–3.1) in 1985 to 1.5 (95% CI: 1.3–1.8) in 2010. Conclusion: Breastfeeding initiation rates have increased; however, this may be due to changes in maternal sociodemographic circumstances. Sociodemographic inequalities in breastfeeding initiation persist and remain of consistent magnitude across the study period, highlighting the need for more targeted strategies.